Dental care of patients undergoing chemo- and radiotherapy - Szyszkowska, Anna; Puławska, Marta; Lewicka, Monika; Koper, Joanna; Malicka, Marta (Contemporary Oncology/Współczesna Onkologia, 2011)
Complete medical and dental care should involve both radio- and chemotherapy’s early and late complications. Therefore, interdisciplinary care and consultations with leading physicians are necessary. Optimal control of side effects of oncological therapy can be obtained only by preliminary preparation of the patient’s oral cavity preceding principal treatment, explaining him the importance of prophylactic activity and the necessity of taking care of oral hygiene rigorously. Precise clinical examination and taking a pantomogram enable the dentist to plan oral cavity sanitation. It is crucial as far as the dental treatment is concerned to eliminate all sources of possible injuries and infections. The dentist’s purpose, if any pathology in the oral cavity appears, is to remove pain, prevent development of infections and facilitate the healing process.